From Awareness to Action: A Predictive Analysis of Green Consumer Preferences in FMCGs in West Bengal (Cuestiones de Fisioterapia, 2025)
The increasing global emphasis on sustainability has led to a transformation in consumer preferences, particularly within the Fast-Moving Consumer Goods (FMCG) sector. As concerns regarding environmental degradation intensify, consumers are becoming more perceptive of the ecological implications of their purchasing decisions, resulting in a growing demand for environmentally responsible products. In this context, it is imperative to examine the determinants that influence consumer preferences for green FMCGs, enabling businesses to formulate effective market strategies.